Selective oxidative dehydrogenation of propane at 380°C by Cs2.5Cu0.08.H3.34PV3Mo 9O40 catalyst precursor - Mizuno, N.; Suh, D.-J. (1996)
Oxidative dehydrogenation of propane was efficiently catalyzed by the Cs2.5Cu0.08H3.34PV3Mo 9O40 catalyst precursor at a reaction temperature as low as 3800C; the selectivity to propene was 25% at a conversion of 40% (10% yield).